Pengaruh Ukuran Perusahaan, Profitabilitas Dan Kebijakan Hutang Terhadap Nilai Perusahaan (Studi pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia yang Terdaftar di BEI Tahun 2017-2019) - Aulia Rizki Dewanti; Ronny Malavia Mardani; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to analyze the effect of firm size, profitability and debt policy on firm value. The method used is correlational associative with a quantitative approach focused on manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange for the period 2017 to 2019 with a sample of 63 companies. The data used is secondary data . The data analysis technique used is multiple linear regression analysis. The results of this study indicate that there is a positive and significant effect of firm size on firm value, there is a positive and significant effect of profitability on firm value and there is a negative but not significant effect of debt policy on firm value in manufacturing companies in the basic and chemical industry sectors listed on the IDX in 2013. 2017 – 2019..  Keywords: Firm Size, Profitability, Debt Policy, Firm Value.